Catching Fish Concept in Balinese Language - Sudana, I Gede Putu (Lingual Journal of Language and Culture; Vol 2 No 2 (2016), 2016)
This paper is intended to explore to what extent the Theory of Natural Semantic Metalanguage can be employed to minimize the ambiguity resulting from different interpretations of the Balinese verbs indicating the action ‘ngejuk bé’ (catching fish). As far as such verbs are concerned, it can be stated that the Balinese language is more sophisticated and richer than Indonesian, as it has so many verb phrases used to refer to the activity of catching fish. The data were collected through the interview and note taking techniques, and were analyzed using Natural Semantic Metalanguage. The result of the study shows that the verbs which can be used to express the activity of ‘ngejuk be’ (catching fish) are ngenyat, mencar, nyau, memancing, nuba, mekena bubu, memancing tungguh, menumbak, nudul and nyuluh, depending on how such an activity is done and what tools are used.
Keywords: catching fish, Natural Semantic Metalanguage